Exploring canyons beneath Devon Ice Cap for sub-glacial drainage using radar and thermodynamic modeling - Chris Pierce; Mark Skidmore; Lucas Beem; Don Blankenship; Ed Adams; Christopher Gerekos (Journal of Glaciology)
Sub-glacial canyon features up to 580 m deep between flat terraces were identified beneath Devon Ice Cap during a 2023 radar echo sounding (RES) survey. The largest canyon connects a hypothesized brine network near the Devon Ice Cap summit with the marine-terminating Sverdrup outlet glacier. This canyon represents a probable drainage route for the hypothesized water system. Radar bed reflectivity is consistently 30 dB lower along the canyon floor than on the terraces, contradicting the signature expected for sub-glacial water. We compare these data with backscattering simulations to demonstrate that the reflectivity pattern may be topographically induced. Our simulated results indicated a 10 m wide canal-like water feature is unlikely along the canyon floor, but smaller features may be difficult to detect via RES. We calculated basal temperature profiles using a 2D finite difference method and found the floor may be up to 18°C warmer than the terraces. However, temperatures remain below the pressure melting point, and there is limited evidence that the canyon floor supports a connected drainage system between the DIC summit and Sverdrup Glacier. The terrain beneath Devon Ice Cap demonstrates limitations for RES. Future studies should evaluate additional correction methods near complex terrain, such as RES simulation as we demonstrate here.